2015
DOI: 10.1002/anie.201504838
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Nanoporous Films from Supramolecular Diblock Copolymers with Hydrogen‐Bonding Junctions

Abstract: We designed efficient precursors that combine complementary associative groups with exceptional binding affinities and thiocarbonylthio moieties enabling precise RAFT polymerization. Well defined PS and PMMA supramolecular polymers with molecular weights up to 30 kg mol(-1) are synthesized and shown to form highly stable supramolecular diblock copolymers (BCPs) when mixed, in non-polar solvents or in the bulk. Hierarchical self-assembly of such supramolecular BCPs by thermal annealing affords morphologies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…We focus on the A5B5 system (consisting of homopolymers A5, a homopolymers chain B5 and diblock polymers A5-B5) and the A3B7 system (consisting of homopolymers A3, homopolymers chain B7 and diblock polymers A3-B7) with supramolecular chain length of N = 10. The size of simulation box is set to 30 × 30 × 30r 3 0 . The random noise amplitude σ = 3.0 and integration time step ∆t = 0.05τ 0 .…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on the A5B5 system (consisting of homopolymers A5, a homopolymers chain B5 and diblock polymers A5-B5) and the A3B7 system (consisting of homopolymers A3, homopolymers chain B7 and diblock polymers A3-B7) with supramolecular chain length of N = 10. The size of simulation box is set to 30 × 30 × 30r 3 0 . The random noise amplitude σ = 3.0 and integration time step ∆t = 0.05τ 0 .…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Supramolecular block copolymers [1] are a type of block copolymers in which polymeric blocks are connected by non-covalent bonds [2]. These non-covalent bonds include multiple hydrogen bonds [3][4][5], host-guest interactions [6], donor acceptor interactions [7], metal-coordination bonds [8][9][10], and so on. Due to the reversible and dynamic nature of non-covalent bonds, supramolecular block copolymers are typically stimuli-responsive.…”
Section: Introductionmentioning
confidence: 99%
“…19 These features of the complementary associative AOA/SOA pair were recently exploited by Bernard and co-workers to design PS-b-PMMA supramolecular diblock copolymers capable to self-assemble into ordered morphologies in bulk and to generate nanoporous films upon cleavage of the hydrogen bonding junction between the two blocks and selective removal of the PMMA domains using specific washing procedures (i.e. [20][21][22] Recently, some of us suggested that AOA-SOA dimers could be advantageously employed for the construction of recodable surfaces. [20][21][22] Recently, some of us suggested that AOA-SOA dimers could be advantageously employed for the construction of recodable surfaces.…”
mentioning
confidence: 99%
“…One example is surface assisted DNA-directed immobilization (DDI) (exploiting hydrogen bonding, as well as the SOA-AOA couple). Onto this wafer (S2) a poly(methyl methacrylate) featuring a SOA terminus (P1) 21 (M nSEC = 29.7 kg mol À1 , Ð = 1.1) is immobilized specifically a Preparative Macromolecular Chemistry, Institut für Technische Chemie und within the AOA-functionalized area based on SOA-AOA dimer formation, via six hydrogen bonds, on the surface yielding S3. Apart from DNA-duplexes, none of the systems rely on hydrogen bonding.…”
mentioning
confidence: 99%
See 1 more Smart Citation